Literature Review: Application Of Plant Dna Barcode Technology: Looks The Same But Is Different - Marlina, Leni; Lestari, Fitria; Asyhar, Rayandra (Jurnal Ilmu Sosial Mamangan, 2024)
Indonesia is famous with megabiodiversity countries or high diversity both flora and fauna. Among the amount types of flora, of course many of which are morphology seen same, will but after seen in a way anatomy or physiology different. Therefore that, it is necessary done identification in a way deep through Use of DNA Barcode for know difference each species existing plants. Purpose from researcher that is to 1) analyze various literature that utilizes DNA Barcode in identification deep species plant certain; 2) knowing methods used; 3) results; and 4) constraints in study from articles that are searched. The method used in study use systematic literature review with method gather articles a type that has been published in online journals through the Google Scholar platform, which is known wide as source reference credible scientific. Based on results review known that there are 20 articles in total specific discuss use of DNA for identify plants. Concluded that visible plants The same in a way morphology, will but if examined more Far with utilizing DNA, then will seen different its type.